Peroxisome proliferator-activated receptors regulate the progression and treatment of gastrointestinal cancers - Zhang, Min; He, Shujie (Frontiers in Pharmacology, 2023)
Peroxisome proliferator-activated receptors (PPARs) are essential nuclear hormone receptors regulating metabolic processes, and they participate in the initiation and progression processes of tumors. Gastrointestinal (GI) cancer is a prevalent malignancy worldwide that originates from the tissues of the gastrointestinal tract and is characterized by severe symptoms and poor prognosis. Numerous published studies have investigated the critical role of PPARs in esophageal, gastric, and colorectal cancers. Here, we summarize and review the current literature to understand the role of PPARs in the pathogenesis of GI cancers and to provide a systematic reference for the subsequent investigation and development of efficient therapies targeting PPARs and their pathways.